2016
DOI: 10.1007/s11069-016-2398-6
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and adaptive capacity of Inuit women to climate change: a case study from Iqaluit, Nunavut

Abstract: This is a repository copy of Vulnerability and adaptive capacity of Inuit women to climate change: a case study from Iqaluit, Nunavut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 82 publications
4
71
0
Order By: Relevance
“…Research examining climate-mental health experiences in Indigenous contexts identified potentially gendered and age-specific mental health outcomes and coping strategies [e.g. 30,57,59,62]. This theme aligns with the broader mental health literature, where mental health outcomes such as suicide and depression, are known to vary by sex and age [89,90].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Research examining climate-mental health experiences in Indigenous contexts identified potentially gendered and age-specific mental health outcomes and coping strategies [e.g. 30,57,59,62]. This theme aligns with the broader mental health literature, where mental health outcomes such as suicide and depression, are known to vary by sex and age [89,90].…”
Section: Discussionsupporting
confidence: 52%
“…27] reported enhanced community cohesion, compassion, and psychological resilience and growth among some individuals. Overall, however, there were no [45,58,59,62,70], two of which investigated women's wellbeing in the context of seasonal and climate-dependent food security [45,70]. Research also indicated that some emotional responses to climate change differed by gender [12,59].…”
Section: How Does Climate Change Impact Indigenous Mental Health?mentioning
confidence: 99%
“…The same study suggests that overcrowding may be perceived as a source of disturbance, and increased pressure on existing building and transport infrastructure and waste facilities that were originally designed to cover basic community needs (ibid.) Shipping can also have negative impacts on Arctic natural environments and sensitive ecosystems (Ford et al, 2018;O'Brien et al, 2006) including those inhabited by marine mammals (Bunce et al, 2016;Christie et al, 2018). refers to Cameron (2012) and argue that "shipping and resource development are likely to be major factors affecting vulnerability and adaptation in Arctic communities."…”
Section: Shipping As An Emerging Changementioning
confidence: 99%
“…Scholarship examining the human dimensions of climate change in the Arctic and Subarctic, particularly in Canada and with a focus on Indigenous peoples is well established (Ford et al 2018 ). Much of this work describes hunting and fishing livelihoods and associated food systems, but comparable work on berry picking is largely absent (Ford et al 2012b ; Bunce et al 2016 ). There are also geographic disparities in research, with most scholarship focusing on communities and the region above 60°N (Ford et al 2012a ) rather than the Subarctic (Downing and Cuerrier 2011 ; Cuerrier et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%